Horse stories in basic vocabulary - Dolch, Edward William 1889-1961 (The Basic vocabulary series, 1958)
Stories, based on actual things horses have done, about all kinds of horses--circus performers, cow ponies, parade horses, work horses, police mounts, race horses, or jumpers.